COVID-19 School Re-opening Plans: Rolling Back School Food Programming in Canada? - Coulas, Mary; Ruetz, Amberley T.; Ismail, Mariam R.; Goodridge, Lindsay H.; Stutz, Sterling; Engler-Stringer, Rachel (Frontiers in Communication, 2022)
School food programs across Canada serve more than 1 million students and provide multifaceted benefits including access to healthy fresh food choices, improving learning capacities, promoting nutritional awareness, assisting food-insecure households, and promoting local food procurement. However, since the beginning of the SARS-Cov 2 (COVID-19) pandemic these programs have faced operational challenges resulting in many rolling back their operations while food insecurity rates in Canada have increased dramatically. Framed as a Canadian case study analysis, this paper considers the reach, effectiveness, adoption, implementation, and maintenance of provincial and territorial school food programs within the broader conceptualization of ecological public health to consider if these programs were enabled or constrained by school reopening plans. The authors conducted a policy analysis of 56 primary and 164 supportive school reopening documents developed between April 2020 and August 2021. It was found that provincial and territorial school reopening plans primarily focused on measures to limit infectious disease transmission while food discussed in broad terms demonstrated policy makers’ limited awareness of the important role of school food programs and support required to maintain them. This paper argues a thorough understanding of the impacts to school food programs by provincial and territorial COVID-19 public health guidelines is needed for politicians, policymakers, and school food practitioners to support the short- and long-term capacity of these programs and to ensure food insecurity and nutritional health issues in Canada continue to be on the political agenda.